Hubungan Sikap dan Minat terhadap Mata Pelajaran PAI dengan Karakter Peserta Didik di Madrasah Ibtidaiyah Negeri (MIN) 10 Ciamis - Ihat, N.; Aziz, Abdul (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2017)
Attitudes and interests of learners to the subjects of PAI ARE factors that contributes to the formation of the character of learners. Learners who have a positive attitude towards PAI subjects are believed to have good character. So also with students who have a high interest in this subject, then he will also have a good character. This is the argument to be the background of this research. The results of this study can be summarized as follows: First, attitudes towards the subjects of Islamic Religious Education are positively related to the character of learners in MIN 10 Ciamis. The better the attitude of learners to the subjects of Islamic Religious Education, the better their character will also be. It is based on correlation test result which yield correlation coefficient number 0,479 (medium correlation). Secondly, interest in the subjects of Islamic Education is positively related to the character of learners in MIN 10 Ciamis. The better the learner's interest in the subjects of Islamic Religious Education, the better their character will be. This is based on the correlation test that yields a correlation coefficient of 0.567 (strong or high correlation). Third, attitude and interest to the subjects of Islamic Religious Education together are positively related to the character of learners in MIN 10 Ciamis. The better the attitudes and interests of learners to the subjects of Islamic Religious Education, the better their character too. It is based on a double correlation test that yields a correlation coefficient of 0.647 (high or strong correlation). Thus, attitudes and interests towards the subjects of Islamic Education contributed 41.8% to the character of learners, and the remaining 58.2% came from other variables